Estimating Levels of Micropollutants in Municipal Wastewater - Rowsell,VF; Tangney,P; Hunt,C; Voulvoulis,N (Water, Air and Soil Pollution, 2010)
Exposure to micropollutants can pose a serious risk to both the environment and human health. Although sewage treatment works (STWs) aim to reduce levels of pollutants in municipal wastewater discharges, they have become a significant point source of dangerous substances to the aquatic environment. With increasing regulation on pollution prevention, it has become essential to assess STW source inputs in order to control pollutant discharge into the environment. This paper has therefore focussed on developing calculations to estimate micropollutant levels in STW influents. The analysis was carried out using information from published literature, the Water Industry, and monitored influent data. Results demonstrated that, where monitoring data were available for metals and organic pollutants, STW influent could be adequately estimated and validated, with accuracy between 77% and 100%. In addition, based on these calculations and using data for over 600 STWs in England, our analysis showed that compounds such as di(2-ethylhexyl) phthalate, lead and linear alkylbenzenesulfonate could reach influent levels that could be challenging for conventional wastewater treatment removal.